Teachers' Perception towards Learner Autonomy in Secondary School (RETAIN, 2020)
The purpose of this study was to gain the teachers’ idea about learner autonomy and significant different of the perception between teacher in urban and rural areas. This study was designed as ex post facto involving 50 secondary English teachers from East Java. In this project the researcher used questionnaire as the instrument which is adapted from Brog and Al-Busaidi (2012). The result of this study showed that the teachers’ perspectives can be divided by 4 categories; technical perspectives, psychological perspectives, political perspectives, and socio-cultural perspectives. Then, from the result of the questionnaire showed that teachers more concern about their political perspectives of learner autonomy. It is determined by the rank of the mean of each category. Political perspectives placed on the first rank with 3.94 as the mean. The researcher find out there are no significant different of the perception of the teachers from urban and rural area for each categories. Keywords: teachers, perception, learner autonomy